Severe Hypotension, Hypoxia, and Subcutaneous Erythema Induced by Indigo Carmine Administration during Open Prostatectomy - Koichiro Nandate; Bryan B. Voelzke (Case Reports in Urology)
Indigo carmine (also known as 5,5′-indigodisulfonic acid sodium salt or indigotine) is a blue dye that is administered intravenously to examine the urinary tract and usually is biologically safe and inert. Indigo carmine rarely may cause adverse reactions. We treated a 66-year-old man who had general anesthesia and radical retropubic prostatectomy for prostate cancer. He had a previous history of allergy to bee sting with nausea, vomiting, and dizziness. Within 1 minute after injection of indigo carmine for evaluation of the ureters, the patient developed hypotension to 40 mmHg, severe hypoxia (the value of SpO2 (peripheral capillary oxygen saturation) was 75% on 40% inspired oxygen concentration), poor air movement and bilateral diffuse wheezing on auscultation, and marked subcutaneous erythema at the upper extremities. After treatment with 100% oxygen, epinephrine (total, 1.5 mg), hydrocortisone (100 mg), diphenhydramine (50 mg), albuterol nebulizer (0.083%), and continuous infusion of epinephrine (0.15 μg/kg/min), the vital signs became stable, and he recovered completely. In summary, indigo carmine rarely may cause life-threatening anaphylactic or anaphylactoid reaction that may necessitate rapid treatment to stabilize cardiovascular, hemodynamic, and pulmonary function.